Journalistic coverage and frames of violence against women in Peru - Prieto-Campos, Carlos (2021)
The study that we present is set within the framework of applied research, to establish the coverage and journalistic frames of violence toward women in Peru; in the newspapers El Comercio, La República and Correo. For this, we made a data record of newspapers from national circulation that was carried in 2020. The method we used was descriptive, following the quantitative line. The design to it corresponds is the simple descriptive one. The data presentation was done through descriptive statistics. The investigation found that the three newspapers cover violence against women. However, it was established that in Correo newspaper the coverage is greater, with respect to El Comercio and La República. The use of the informative journalistic gender was the most used by newspapers for their reports; while in the frames, the one that stands out the most was the attribution of responsibility and the one with the least use, was the economic consequences.